The relationship of thinking styles and academic performance of students - O. A. Khalifaeva; N. Yu. Kolenkova; I. Yu. Tyurina; A. G. Fadina (Образование и наука)
Introduction. In the conditions of modern Russian education, the emphasis is shifted to the ability of students to carry out non-standard professional duties and to work independently. All this leads to an increase in the number of studies to identify thinking styles in the student age.The aim of the current publication is to present the results of an empirical study focusing on identification of the relationship of thinking styles and academic performance among the students of Astrakhan State University.Methodology and research methods. In order to achieve the aim, the authors used the following research methods: Methods of Thinking Style (by A. K. Belousova), Learning Styles Questionnaire (by P. Honey, A. Mumford), Implicit Theories and Learning Goals Questionnaire (by C. Dweck), Scale of Academic Motivation (by T. O. Gordeeva, O. A. Sychev, E. N. Osin). To process the data, mathematical-statistical methods were employed: the One-Sample Kolmogorov-Smirnov Test, the Independent Samples t Test (Student Test), the Mann-Whitney U Test, the Pearson’s Correlation Coefficient, the Spearman’s Rank Correlation Coefficient. All calculations were performed using the IBM SPSS Statistics 21 computer program.Results. In the course of empirical study, 82 students of five faculties of Astrakhan State University (40 boys and 42 girls aged 20 to 23 years old) were involved. As a result of empirical research, it was revealed that an initiative style of thinking with the variable “enriched personality” has a positive correlation, and critical thinking has a positive correlation with the variable “introjected motivation” and “external motivation”. Managerial and practical thinking styles positively correlate with the variables “achievement motivation”, “growing in telligence”, “enriched personality”, “cognitive motivation”, “adoption of learning goals”.Scientific novelty. The tendency to a reliable connection of thinking styles and academic performance was revealed. A positive correlation between managerial, practical thinking styles and cognitive motivation, achievement motivation is found out. Students with proactive, practical, managerial thinking styles have an above-average academic performance.Practical significance. The materials of the publication are of practical importance for teachers and students, as the study of the stylistic peculiarities of the individuality of students directly contributes to the effectiveness of the process of skills and knowledge development.